Pharmacists’ Perceived Barriers to Human Papillomavirus (HPV) Vaccination: A Systematic Literature Review - Oluwafemifola Oyedeji (MDPI AG, 2021)
About 45:000 cancers are linked to HPV each year in the United States alone. The HPV vaccine prevents cancer and is highly effective, yet vaccination coverage remains low. Pharmacies can play a meaningful role in increasing HPV vaccination access due to their availability and convenience. However, little is known about pharmacists’ perceived barriers to HPV vaccination. The objective of this systematic review was to summarize existing literature on perceived barriers to administering HPV vaccination reported by pharmacists. Barriers identified from selected studies were synthesized and further grouped into patient, parental, (pharmacist’s) personal, and system/organization barrier groups. Six studies were included in this review. The cost of the HPV vaccine, insurance coverage and reimbursement were commonly reported perceived barriers. Adolescent HPV vaccination barriers related to parental concerns, beliefs, and inadequate knowledge about the HPV vaccine. Perceived (pharmacist’s) personal barriers were related to lack of information and knowledge about HPV vaccine and recommendations. At the system/organization level, barriers reported included lack of time/staff/space; difficulty in series completion; tracking and recall of patient; perceived competition with providers; and other responsibilities/vaccines taking precedence. Future strategies involving pharmacy settings in HPV-related cancer prevention efforts should consider research on multilevel pharmacy-driven interventions addressing barriers.